NCIA-AMB MASUK KAMPUNG PROJECT: A PARADIGM OF OPPORTUNITIES AND CHALLENGES FOR SUSTAINABLE RURAL DEVELOPMENT - Malik, Sana; Khilat, Faiqa; Tariq, Fariha; Ariffin, Kamal (PLANNING MALAYSIA, 2018)
Malaysian government is focused to accomplish world-class living standard of whole nation by year 2025 through sustainable development irrespective of regional, religious and ethnic boundaries. The Northern Corridor Implementation Authority (NCIA) is an organization set up for the implementation of Koridor Utara (Northern Corridor Economic Region, NCER) in Malaysia for achieving this vision. Such economic corridors are aimed to elevate the income levels through agriculture, manufacturing, logistics, education and tourism. The execution of development projects always impact the involved community in multiple dimensions. Masuk Kampung Project at Pantai Murni, Yan Kedah was one of the NCIA initiatives in collaboration with AMB (Akademi Binaan Malaysia). This paper draws out a conceptual framework of community perceptions associated with this project based on qualitative research. Viewpoints studied through interviews and participant observation helped in fabricating the opportunities and challenges connected with rural development. Findings revealed that community perception is of key importance and their prime reflections can be beneficial to policy makers, stakeholders, academicians and civil society in shaping the policy agenda for future projects of same nature in Malaysia. Hence, the study is a contribution to understanding development projects aiming at rural areas on national and global channels.